Examination of the Impact of Facility and Infrastructure Quality on Tourist Satisfaction at the Kacirebonan Palace - Riyanto Wibowo; Widia Ningsi (Ann Publisher, 2025)
Background. Kacirebonan Palace is a tourist destination in Cirebon City that offers cultural attractions, building attractions, typical food, and drinks, making it an attraction for tourists visiting Cirebon City. Purpose. This study aims to determine the influence of facilities and infrastructure owned by the Kacirebonan Palace on the satisfaction of tourists who come to the Kacirebonan Palace Method. The study used a quantitative method in SPSS version 23 to determine the influence of variables, using questionnaire data collected from 97 people who attended the Kacirebonan Palace, and employed accidental sampling. Conclusion. The results of this study indicate that facilities and infrastructure significantly influence tourist satisfaction at the Kacirebonan Palace, although the Palace still needs to improve its provision of adequate facilities and infrastructure for visitors.